2003
DOI: 10.1111/j.1365-2567.2003.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune response to encephalomyocarditis virus infection mediated by CD1d

Abstract: SUMMARYCD1d-reactive natural killer T (NKT) cells can rapidly produce T helper type 1 (Th1) and/or Th2 cytokines, can activate antigen-presenting cell (APC) interleukin-12 (IL-12) production, and are implicated in the regulation of adaptive immune responses. The role of the CD1d system was assessed during infection with encephalomyocarditis virus (EMCV-D), a picornavirus that causes acute diabetes, paralysis and myocarditis. EMCV-D resistance depends on IL-12-mediated interferon-g (IFN-g) production. CD1d-de®c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
92
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 67 publications
9
92
0
Order By: Relevance
“…(129 Â C57BL/6) F2 CD1d KO mice [50] were immunized i.p. and s.c. with invariant peptide-KLH and CFA, boosted 4-6 wk later with invariant peptide-BSA and IFA, and reboosted i.v.…”
Section: Isolation Of Invariant Tcr Cdr3 Loop-specific Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…(129 Â C57BL/6) F2 CD1d KO mice [50] were immunized i.p. and s.c. with invariant peptide-KLH and CFA, boosted 4-6 wk later with invariant peptide-BSA and IFA, and reboosted i.v.…”
Section: Isolation Of Invariant Tcr Cdr3 Loop-specific Antibodiesmentioning
confidence: 99%
“…Imject TM -activated KLH, BSA, or OVA coupling was performed as recommended by the manufacturer (Pierce, Rockford, IL). (129 Â C57BL/6) F2 CD1d KO mice [50] were immunized i.p. and s.c. with invariant peptide-KLH and CFA, boosted 4-6 wk later with invariant peptide-BSA and IFA, and reboosted i.v.…”
Section: Isolation Of Invariant Tcr Cdr3 Loop-specific Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 However, iNKT cells do not seem to participate in anti-viral immunity or control of viral replication during infection with encephalomyocarditis virus and murine cytomegalovirus. [35][36][37] The potential role of iNKT cells in experimental viral infections has also been studied using CD1d-deficient mice, which lack both iNKT cells and vNKT cells. Although it is not possible to differentiate between a role of iNKT cells, vNKT cells, or the CD1d molecule, comparison of CD1d-competent and CD1d-deficient mice has suggested that NKT cells might positively contribute to the immune response to infection with respiratory syncytial virus, Theiler's murine encephalomyelitis virus, encephalomyocarditis virus, and murine cytomegalovirus.…”
mentioning
confidence: 99%
“…Although it is not possible to differentiate between a role of iNKT cells, vNKT cells, or the CD1d molecule, comparison of CD1d-competent and CD1d-deficient mice has suggested that NKT cells might positively contribute to the immune response to infection with respiratory syncytial virus, Theiler's murine encephalomyelitis virus, encephalomyocarditis virus, and murine cytomegalovirus. 35,[37][38][39] Although there are relatively few iNKT cells in the human system, there is evidence for an antiviral role of these cells. 40 -43 Of note, the potential role of NKT cells during flavivirus infection has not yet been addressed.…”
mentioning
confidence: 99%